Exploring concordance and discordance for return of incidental findings from clinical sequencing - Green, Robert C.; Berg, Jonathan S.; Berry, Gerard T.; Biesecker, Leslie G.; Dimmock, David P.; Evans, James P.; Grody, Wayne W.; Hegde, Madhuri R.; Kalia, Sarah; Korf, Bruce R.; Krantz, Ian; McGuire, Amy L.; et al. (Genetics in medicine, 2012)
Purpose: The aim of this study was to explore specific conditions and types of genetic variants that specialists in genetics recommend should be returned as incidental findings in clinical sequencing. Methods: Sixteen specialists in clinical genetics and/or molecular medicine selected variants in 99 common conditions to return to the ordering physician if discovered incidentally through whole-genome sequencing. For most conditions, the specialists independently considered three molecular scenarios for both adults and minor children: a known pathogenic mutation, a truncating variant presumed pathogenic (where other truncating variants are known to be pathogenic), and a missense variant predicted in silico to be pathogenic. Results: On average, for adults and children, respectively, each specialist selected 83.5 and 79.0 conditions or genes of 99 in the known pathogenic mutation categories, 57.0 and 53.5 of 72 in the truncating variant categories, and 33.4 and 29.7 of 72 in the missense variant categories. Concordance in favor of disclosure within the adult/known pathogenic mutation category was 100% for 21 conditions or genes and 80% or higher for 64 conditions or genes. Conclusion: Specialists were highly concordant for the return of findings for 64 conditions or genes if discovered incidentally during whole-exome sequencing or whole-genome sequencing. Genet Med 2012:14(4):405–410